British literature and technology, 1600-1830 - Girten, Kristin M.; Hanlon, Aaron R. (Aaron Raymond), 1982-; Project Muse. (Lewisburg, Pennsylvania : Bucknell University Press, 2023)
"Enlightenment-era writers had not yet come to take technology for granted, but nonetheless were--as we are today--both attracted to and repelled by its potential. This volume registers the deep history of such ambivalence, examining technology's influence on Enlightenment British literature, as well as the impact of literature on conceptions of, attitudes toward, and implementations of technology. Offering a counterbalance to the abundance of studies on literature and science in seventeenth- and eighteenth-century Britain, this volume's focus encompasses approaches to literary history that help us understand technologies like the steam engine and the telegraph along with representations of technology in literature such as the 'political machine.' Contributors ultimately show how literature across genres provided important sites for Enlightenment readers to recognize themselves as 'chimeras'--'hybrids of machine and organism'--and to explore the modern self as 'a creature of social reality as well as a creature of fiction.'"--
Introduction / Kristin M. Girten and Aaron R. Hanlon -- 1. Webster's baroque experiments and the testing of technology in the early 1600s / Laura Francis -- 2. Telling time in the fiction of Mary Hearne and Daniel Defoe / Erik L. Johnson -- 3. The technology and theatricality of Three Hours after Marriage's "touch-stone of virginity" / Thomas A. Oldham -- 4. Gulliver's Travels, automation, and the reckoning author / Zachary M. Mann -- 5. Designing the Enlightenment Anthropocene / Kevin MacDonnell -- 6. Technology, temporality, and queer form in Horace Walpole's Gothic / Emily M. West -- 7. Telegraphic supremacy in Maria Edgeworth's "Lame Jervas" / Deven M. Parker -- 8. Percy Shelley, political machines, and the prehistory of the postliberal / Jamison Kantor -- Afterword: On the uses of the history of technology for literary studies and vice versa / Joseph Drury.
Includes bibliographical references and index.
KRISTIN M. GIRTEN is an associate professor of English and assistant vice chancellor for the arts and humanities at the University of Nebraska at Omaha. AARON R. HANLON is an associate professor of English and chair of the Science, Technology, and Society Program at Colby College in Waterville, Maine.
Print version record.
JSTOR
Keywords: English literature -- 17th century -- History and criticism; English literature -- 18th century -- History and criticism; English literature -- 19th century -- History and criticism; Literature and technology; English literature -- Early modern, 1500-1700 -- History and criticism; Littérature anglaise -- 17e siècle -- Histoire et critique; Littérature anglaise -- 18e siècle -- Histoire et critique; Littérature anglaise -- 19e siècle -- Histoire et critique; Littérature et technologie; LITERARY CRITICISM / General; Literature and technology; English literature; 1600-1899; Electronic books; Literary criticism; Criticism, interpretation, etc; Literary criticism; Critiques littéraires.